Adaptability Studies on Few Groundnut Genotypes - Sanjeeviah, B S; Rajashekara, B G; Krishnamurthy, K (Annals of Arid Zone, 2016)
Adaptability studies wee conducted on eleven bunch type groundnut under dry land conditions at Agricultural Research Station, Hebbal on red loamy soils. The genotypes included were; (1) AK-12-24 (Maharastra), (2) Faizpur, (3) Spanish Improves; (4) T.M. V-2, (5) Exotic-5, (6) AK 12-24 (Madhya Pradesh), (7) C-501, (8) SB-11, (9) H. G-8, (10) HG-10 and (11) Local S-206. Though Faizpur and AK-12-24 were heavy yielders, they were found to give lower performance in years of low rain fall and had lower adaptability. Spanish Improved grave nearly 14 per cent more yield than HG-8, a recommended variety of the locality, ant it had higher adaptability.